ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARI’AH MENGGUNAKAN PENDEKATAN INCOME STATEMENT (ISA) DAN VALUE ADDED REPORTING (VAR) (Universitas Negeri Semarang, 2013)
The purpose of this study to assess the financial performance of shariah bank if the income is calculated by the approach (ISA) and the value added (VAR). Samples used in this study are the annual financial statements of listed BUS in 2008-2010 in BI., And taken by purposive sampling method. Methods of data analysis is done using several statistical techniques including descriptive analysis with different test parametric statistical approach is to test Independent Sample t Test .. These results suggest that intellectual capital affect financial performance and market value. These results indicate that the financial performance of BUS-year period 2008-2010, in which case the value of ROA, ROE, and NPM LBAP there are significant differences. Although quantitatively the magnitude of the four ratios in VAR under the ISA. BOPO whereas there were no significant differences. This is because operating income and operating expenses in the VAR are treated as fixed in the ISA